Teknik Manajemen Waktu yang Efektif Untuk Mengatasi Stres Dalam Industri - Mila Hariani; Wulandari; Rahayu Mardikaningsih; Eli Masnawati; Uswatun Chasanah (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
Effective time management in the industrial workplace is key to reducing the high levels of stress that workers often face. In a competitive and dynamic industrial environment, good time management can help individuals organize their tasks and responsibilities more efficiently, thereby reducing stress and improving mental and physical well-being. Various time management techniques have been developed and implemented by individuals in the industry to overcome these challenges. This includes prioritizing tasks, using effective time planning, task delegation, setting deadlines, and utilizing technology. However, the effectiveness of these techniques may vary depending on individual preferences, work culture, and the physical environment of the workplace. Additionally, it is important to understand differences in the application of time management techniques between industries, taking into account different job demands, work cultures, and company policies. Implementing appropriate time management techniques can help individuals reduce stress levels and increase productivity, while paying attention to these factors also helps organizations create a more sustainable and competitive work environment.